Intergenerational and gender relations in albanian migrant families. The example of household labour division - Thanopoulou, Maria (The Greek Review of Social Research, 2007)
<div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 398.206px; transform: rotate(0deg) scale(0.988811, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.7190269756317">Household labour division in Albanian migrants’ families living in Athens constitutes <div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 417.684px; transform: rotate(0deg) scale(1.06015, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="467.2430670059204">an interesting example illustrating the evolution of intergenerational and gender <div style="font-size: 13.4949px; font-family: serif; left: 111.783px; top: 437.161px; transform: rotate(0deg) scale(0.972268, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.6886669738769">relations, as these develop under the influence of the labour market conditions. Using <div style="font-size: 13.4949px; font-family: serif; left: 111.783px; top: 456.624px; transform: rotate(0deg) scale(0.952415, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.6833869735717">the life stories of twenty five members of Albanian families, the present article focuses <div style="font-size: 13.4949px; font-family: serif; left: 111.782px; top: 476.101px; transform: rotate(0deg) scale(1.00499, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.3151069522858">on household labour division, as it figures in three generations: the grandparents in <div style="font-size: 13.4949px; font-family: serif; left: 111.782px; top: 495.579px; transform: rotate(0deg) scale(0.958368, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.7573069778442">Albania, the parents-migrants and the children-migrants. To start with, it describes the <div style="font-size: 13.4949px; font-family: serif; left: 111.781px; top: 515.057px; transform: rotate(0deg) scale(0.978339, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.6675469726562">existing situation per generation, emphasising the role distribution per gender and the <div style="font-size: 13.4949px; font-family: serif; left: 111.781px; top: 534.535px; transform: rotate(0deg) scale(0.994317, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="467.32886701087955">subsequent distribution of power per gender and per generation. Then, it points out <div style="font-size: 13.4949px; font-family: serif; left: 111.781px; top: 553.997px; transform: rotate(0deg) scale(1.08274, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="468.24890706405625">some emerging intergenerational tendencies of changes observed in the <div style="font-size: 13.4949px; font-family: serif; left: 111.78px; top: 573.475px; transform: rotate(0deg) scale(0.98725, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="466.70582697486884">intergenerational and gender relations. The article concludes by drawing attention to <div style="font-size: 13.4949px; font-family: serif; left: 111.779px; top: 592.953px; transform: rotate(0deg) scale(0.94416, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_114_0" data-canvas-width="394.6589028106688">those aspects of household labour division requiring further investigation.